Modelling roughness of road profiles on parallel tracks using roughness indicators. (2016) - Johannesson, Par; Podgórski, Krzysztof; Rychlik, Igor
The vertical road input is the most important load for durability assessments of vehicles. We focus on stochastic modelling of the parallel road profiles with the aim to find a simple but still accurate model for such bivariate records. A model is proposed that is locally Gaussian with randomly gamma distributed variances leading to a generalised Laplace distribution of the road profile. This Laplace model is paired with the ISO spectrum and is specified by only three parameters. Two of them can be estimated directly from a sequence of roughness indicators, such as IRI or ISO roughness coefficients. The third parameter, needed to define the cross-spectrum between the left and right road profiles, is estimated from the sample correlation. Explicit approximations for the expected fatigue damage for the proposed Laplace-ISO model are developed. The usefulness of the methods is validated using measured road profiles.